(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2025)
Presently, polypropylene (PP), a type of thermoplastic polymer, becomes favorable for use in power cable insulation owing to its better electrical properties over the thermoset crosslinked polyethylene (XLPE). However, PP has a significant issue in term of mechanical properties. Specifically, standalone PP has high stiffness and brittleness. Therefore, adding copolymers into PP is an effective approach to tailor the flexibility of standalone PP. Nevertheless, this often comes with degraded dielectric strength of PP/copolymer blends, particularly with increasing loadings of copolymers. Therefore, this paper investigates the chemical structure and AC and DC breakdown performance of PP with 20 wt% of ethylene-based copolymer (EBC) and 20 wt% of propylene-based copolymer (PBC). The results reveal that the presence of methyl groups of PP/EBC is more pronounced compared to PP/PBC. Meanwhile, the AC breakdown strengths of PP with 20 wt% of EBC and 20 wt% of PBC are comparable at 151 kV/mm and 153 kV/mm respectively, compared to that of XLPE (148 kV/mm). Additionally, PP with 20 wt% of EBC has a comparable DC breakdown strength (317 kV/mm) to XLPE (324 kV/mm) while PP with 20 wt% of PBC has a higher DC breakdown strength (338 kV/mm) over XLPE. Therefore, both the AC and DC breakdown performance of PP with 20 wt% of EBC and 20 wt% of PBC are not inferior over XLPE. These suggest that 20 wt% of EBC and 20 wt% of PBC are appropriate for formulating PP/EBC blend and PP/PBC blend as alternatives to XLPE.